THE EFFECT OF THE STORY BOOK USAGE TOWARD THE COMMUNICATION ABILITY OF CHILD WITH AUTISM - Arie Lusiati; Wiwik Dwi Hastuti (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2016)
The purposes of this research were to describe: (1) the communication ability of children with autism before using a story book, (2) the communication ability of children with autism after using a story book, (3) the significant effect between story book for the communication ability of children with autism. The research design was experiment method with the single subject (Single Subject Research) and A-B-A’ design. The data was collected by using an assessment and observation. It has been collected by percentage. Based to the result, the mean level was 85.7 in intervention condition. Overlap percentage was 0%, it has showed that the intervention with telling story by the story book had an effect to the behavior’s target of communication ability. It could increased the communication ability of children with autism. The conclusion of this research showed that by using the story book can increase the communication ability of children with autism after getting intervention by using the story book. The suggestion for the teacher should use a media such as a story book that based on the theme to increase the communication of children with autism